(x+8)(x-3)=126

Simple and best practice solution for (x+8)(x-3)=126 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)(x-3)=126 equation:



(x+8)(x-3)=126
We move all terms to the left:
(x+8)(x-3)-(126)=0
We multiply parentheses ..
(+x^2-3x+8x-24)-126=0
We get rid of parentheses
x^2-3x+8x-24-126=0
We add all the numbers together, and all the variables
x^2+5x-150=0
a = 1; b = 5; c = -150;
Δ = b2-4ac
Δ = 52-4·1·(-150)
Δ = 625
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{625}=25$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-25}{2*1}=\frac{-30}{2} =-15 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+25}{2*1}=\frac{20}{2} =10 $

See similar equations:

| 2v-6v=1 | | (x+8)=(9x) | | 2a+9-7=9 | | -9=(2/5m)+7 | | 15+50p=25+.25p | | 15+50p=25+.25 | | 1x/5+2/5=12 | | -d—13d+6=18 | | .25x+0.05(x+2)+0.1(3x)=36 | | 15x+2=10x+6 | | X-5/2-x+1/3=1/6 | | 0.50x+10.5=35.5 | | 1/5x+2/5=12 | | 54=5x+6-x | | 8-2(4x-6)=-60 | | (9x+7)=(x+7)2 | | d/4+2=5 | | 164-u=207 | | 2=p-4/3 | | x-135=177-11x | | 3(x-6)=48 | | 20m-8m-3=-15 | | 91/12=12g | | 4x+8=4x+3x | | 3x=8-12x/8+2 | | x/2.8+4.9=7 | | d/2-10=8 | | 3(5x+9)=-37+34 | | -6x+-28=2x+12 | | -2c−1=c−7 | | 4p+3p=20+2p | | -18+18y=20y |

Equations solver categories